IMPLIKASI AJARAN RAMAYANA DALAM BERSOSIALISASI PADA ERA DIGITAL DAN RELEVANSINYA TERHADAP MODERASI BERAGAMA - Nusantari, Ni Putu Nirani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research is qualitative descriptive research that takes the implication of the Ramayana story in the digital era as an object and its relevance in religious moderation. The data collection method used in this study is the method of observation and literature study. The summary of the Ramayana story taken in the Itihasa book in this paper, is found to have strong relevance in today's society, especially in the era of the industrial revolution 4.0 and the stage of entering the era of society 5.0 which is inseparable from the existence of technology. The story of the Ramayana also has relevance to the application of religious moderation in today's society, so that it can be used as a reference in life